PARENTS BECOME THE BASIS OF BUILDING CHILD INDEPENDENCE - Muhammad Syafiqi Ramananda; Shokhibul Wajhil Munir (FKIP, Universitas Palangka Raya, 2023)
This study aims to determine the parenting style of parents in building children's independence, because the role of parents is very important in building independence in children. Education in early childhood is an effort to stimulate, guide and provide learning aimed at developing skills in children. Parents as caregivers of children must have an understanding of their child's development. The development of children's intelligence at an early age develops optimally at the age of 4 years. Along with these developments, children will actively move, imitate units, or say something to interact with those around them. Therefore, the development of a child is influenced by the treatment of parents and families towards him.